Exploring the place of financial status in the good life: Income and meaning in life. Issue 3 (4th May 2019) - Ward, Sarah J.; King, Laura A.
Abstract: Two studies examined the association between income and meaning in life (MIL). Study 1 ( N  = 781) demonstrated that income and other measures of financial status are positively associated with MIL and other aspects of well-being. The association between income and MIL was partially explained by autonomy, competence, and perceptions of control. Study 2 ( N  = 123) examined people's forecasts of how financial status would affect their future well-being. Having a middle class or upper-middle class income in the future was expected to result in higher MIL, happiness, and need satisfaction than a life with a low income, showing that people perceive income as tied to meaning. These studies demonstrate how financial status can contribute to actual and expected MIL.